Do different methods yield equivalent estimations of brain size in birds? - Ocampo Vargas, Diego (2020)
The ratio of brain size to body size (relative brain size) is often used as a measure of relative investment in the brain in ecological and evolutionary studies on a wide range of animal groups. In birds, a variety of methods have been used to measure the brain size part of this ratio, including endocranial volume, fixed brain mass, and fresh brain mass. It is still unclear, however, whether these methods yield the same results. Using data obtained from fresh corpses and from published sources, this study shows that endocranial volume, mass of fixed brain tissue, and fresh mass provide equivalent estimations of brain size for 48 bird families, in 19 orders. We found, however, that the various methods yield significantly different brain size estimates for hummingbirds (Trochilidae). For hummingbirds, fixed brain mass tends to underestimate brain size due to reduced tissue density, whereas endocranial volume overestimates brain size because it includes a larger volume than that occupied by the brain.